KEY INSIGHT ON THE USE OF IMPROVED MILLET AND GROUNDNUT VARIETIES IN DRYLAND AREAS OF SENEGAL - Diouf, Abdoul Mouhamed; Thiaw, Moussa; Houessionon, Prosper; Akinseye, Folorounsho; Worou, Nadine; Wane, Abdrahmane (International Livestock Research Institute, 2024)
This study investigates the impact of improved millet and groundnut varieties on smallholder farmers' productivity in Senegal. It explores adoption factors and yield effects by analyzing data from 21 villages in Kaffrine, Louga, and Thiès regions. Climate- Smart Agriculture training emerges as the primary adoption driver, increasing adoption probabilities by 21.8% for millet and 26.6% for groundnut. Improved varieties significantly boost millet yields by 91% (+360 kg/ha), while groundnut yields increase by 40% (+180 kg/ha), though not statistically significant. Aligning to Ricciardi et al. (2020), the findings underscore the positive impact of agricultural technologies and emphasize the need to understand adoption factors better. Recommendations include enhancing training access, tailoring agricultural strategies to local contexts, and considering socioeconomic and gender factors to optimize farm productivity and maximize innovation benefits.